Desenvolvimento de protocolo de propagação de espécies de Melocactus em situação de risco de extinção - Santos, Raquel Lima (2019)
The environment suffers most from the impact of different factors, such as extractivism, deforestation was developed by anthropic action. The current situation has caused the greatest loss of riches of the natural fauna and flora that once existed. They have specific behaviors that decrease the probability of occurrence of cacti in the state of Sergipe, where endangered species may be found. Among the aggravating factors that influence this issue are deforestation for real estate purposes and the raising of animals, as well as the extraction of the landscape that has been growing in a disorderly way in recent years. These factors were linked to a seed germination rate and to the endemism occurring in nature, contributing to a drastic reduction of the population in the state of Sergipe, attenuating and unbalancing the ecology of the Caatinga biome and committing to a biodiversity. To have a view this situation, the present work has proprocess to program protocol for sexual propagation and understand the partner socioeconomic that is prepared in context. Species and fruits of species of the genus are in extinction conditions and in different levels of energy. After the first anamnesis, the germination tests as a function of the relative air pain; storage of seeds as a function of temperature and time; The evaluation of plant in the substrate and the size of container. The following themes were adapted for the application of semi-structured questionnaires aimed at the prototypes with the species of Melocactus. The expected results have been a definition of the propagation protocol to be used by the organ of foment to the storage of the species. and the degree of interference of the population in relation to the studied genre.